Algebra

Páginas: 2 (426 palabras) Publicado: 22 de marzo de 2011
Trinomio General
99. x^2-3x-18=(x-9)(x+2)

100. x^2-9x+14=(x-7)(x-2)

101. x^2-9x+14=(x+8)(x-3)

102. 15-2x-x^2=(3-x)(5+x)

103.24+2x-x^2=(6-x)(4+x)

104. 4+5h-6h^2=(1+2h)(4-3h)

105. 28a^3-45a+18=(-7a^2+6)(-4a+3)

106. 9y^2-40y+16=(-9y+4)(-y+4)

107. m^2n^2+3mn-10=(mn-2)(mn+5)

108. 〖25a〗^2 x^2+20ax+4=(5ax+2)(5ax+2)=〖(5a+2)〗^2

109. 〖9a〗^2 b^2-9abc-10c^2=(-3ab+2c)(3ab+5c)

110.9a^2-24xy+16y^2=(3x-4y)(3x-4y)=〖(3x-4y)〗^2

111. 9a^2-30ab+16b^2=(-3a+8b)(-3a+2b)

112. 16x^2-16xy-21y^2=(4x+3y)(4x-7y)

113. 28a^2-45a+18=(4a-3)(7a-6)

114.4+5h-6h^2=(1+2h)(4-3h)

115. 2-3x-20x^2=(1-4x)(2+5x)

116. x^4+x^2-6=(x^2-2)(x^2+3)

117. 〖p4+2p〗^2 q^2-3q^4=(p^2-q)(p^2+3q)

118. 〖9b〗^4-〖4b〗^2c-5c^2=(b^2-c)(〖9b〗^2+5)

119. 49+14a^2-15a^4=(7-3a^2 )(7+5a^2)

120. 〖12x〗^4 y^2+11〖ax〗^2 y-36a^2=(〖3x〗^2 y-4a)(〖4x〗^2 y+9a)

121.〖(m-n)〗^2-(m-n)-2=((m-n)+1)((m-n)-2)

122. 3〖(x+y)〗^2-7(x+y)+2=(1(x+y)-2)(3(x+y)-1)
Suma y Diferencia de Cubos
123. 125a^3+8b^3=(5a+2b)(25a^2+10ab+2b)

124.27y^3-64x^3=(5a+2b)(9y^2-12yx+16x^2)

125. 64+x^3 y^3=(4+xy)(16+4xy+x^2 y^2)

126. 8〖(a+b)〗^3+1=(2(a+b)+1) 〖(4(a+b)〗^2+2(a+b)+1)

127.〖(x+1)〗^3-8x^3=((x+1)-2x)((x+1)^2-(2x^2-2x)+4x^2)

128. x^3+〖(2y+5)〗^3=(x+(2y+5) )(x^2+(2xy+5x)+(2y+5)^2)

129. y^6+x^6=(y^3+x^3 )(y^3 x^3)

130.m^6-n^6=(m^3+n^3 )(m^3+n^3)

131. x^9-〖(y-z)〗^6=(x^4-(y-z)^3 )(x^5-〖(x〗^5 ) 〖(y-z)〗^3-〖(y-z)〗^3)

132. 27x^9+8=(3x^4+2)(9x^5+6x^4+4)

Regístrate para leer el documento completo.